Determinan Nilai Tukar Rupiah di Indonesia - Rurin Mey Dwidowati; Theresia Militina; Agus Junaidi (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
Rurin Mey Dwidowati, 2019 Determinant of the Rupiah Exchange Rate in Indonesia under the guidance of Mrs. Theresia Militina and Mr. Agus Junaidi. The rupiah exchange rate in Indonesia experienced fluctuations from 2006 to 2018. This study aims to examine and analyze the determinants of the rupiah exchange rate in Indonesia. The theory used in this study is the purchasing power parity theory by David Ricardo. Data used in the form of time series data with a span of 13 years. The analysis technique used is multiple regression analysis. The results showed that inflation had no significant effect on the rupiah exchange rate in Indonesia in 2006-2018. Interest rates have a significant effect the rupiah exchange rate in Indonesia in 2006-2018. Foreign exchange reserves have a significant effect on the rupiah exchange rate in Indonesia in 2006-2018.